The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1029/2019jb018900
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic and Sedimentary Structure beneath the Klyuchevskoy Volcanic Group, Kamchatka, From Ambient Noise Tomography

Abstract: The Klyuchevskoy Volcanic Group is a cluster of the world's most active subduction volcanoes, situated on the Kamchatka Peninsula, Russia. The volcanoes lie in an unusual off‐arc position within the Central Kamchatka Depression (CKD), a large sedimentary basin whose origin is not fully understood. Many gaps also remain in the knowledge of the crustal magmatic plumbing system of these volcanoes. We conducted an ambient noise surface wave tomography, to image the 3‐D shear wave velocity structure of the Klyuchev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 64 publications
(100 reference statements)
3
31
0
Order By: Relevance
“…In the crust, the model is generally consistent with the previous study by Koulakov et al (2017), because at shallow depths, the tomography is mostly controlled by the same subsets as used in the previous case. We also observe some correspondence with the new results of the ambient noise tomography (Green et al, 2020, and especially with Egorushkin et al, 2020).…”
Section: Tomography Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In the crust, the model is generally consistent with the previous study by Koulakov et al (2017), because at shallow depths, the tomography is mostly controlled by the same subsets as used in the previous case. We also observe some correspondence with the new results of the ambient noise tomography (Green et al, 2020, and especially with Egorushkin et al, 2020).…”
Section: Tomography Resultssupporting
confidence: 90%
“…It is unlikely that such amount of subsidence occurred merely due to isostatic compensation caused by the volcanic mass growing, as proposed by Melekestsev (1980). Green et al (2020) proposed that the CKD subsidence and accumulation of sediments occurred in two stages. The first stage was related to relatively slow formation of the fore‐arc basin during Eocene‐Pliocene, when Sredinny Range acted as the main volcanic arc (Avdeiko et al, 2007; Portnyagin et al, 2005).…”
Section: Discussion and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data of permanent seismic stations operated by the KBGS and several temporary seismic networks installed in the vicinity of Bezymianny and its neighboring volcanoes of the KGV, previous studies [29][30][31][32][33][34][35] revealed multilevel magma storages in the crust and the uppermost mantle: the shallow-most level being located at circa 8 km depth. Multiple petrological studies 36,37 revealed consistent storage conditions of magmas for Bezymianny, but they could not yet characterize the lateral complexity and dimensions of potential reservoirs.…”
Section: Bezymianny Volcanomentioning
confidence: 99%
“…The temporary network included 30 sensors Trillium Compact (period of up to 120 s), six Guralp CMG-6T (30 s period), eight Guralp-CNG-6TD (30 s period), nine CME-4111 (30 s period), and 30 Mark L-4C-3D with the nominal period of 1 s, which can be extended up to 20 s. All stations recorded three-component seismograms with the sample rate of 100 Hz. More details on the network are described in Green et al (2020). The network operated until July 2016.…”
Section: Data Description and Algorithmmentioning
confidence: 99%